Final Report : CreateED : Strengthening Learning and Teaching Leadership in the Creative Arts. - de la Harpe, Barbara; Mason, Thembi (Office for Learning and Teaching, 2014)
Final report from the CreateED project that aimed to strengthen learning and teaching across Australian creative arts disciplines, including architecture, creative writing, design, performing arts (dance and music), and visual arts. The project facilitated those in learning and teaching leadership roles nationally to work together strategically to enhance their leadership capability, to address issues of learning and teaching importance, and to contribute publications on leadership to the scholarship of teaching and learning. The development of leadership capability was both a focus and an outcome of the project through individuals joining forces to (re)position, promote, enhance, and influence institutional and discipline-specific learning and teaching practices, as a strategic knowledge network: Create.ED.